Corrosion performance of laser post-treated cold sprayed titanium coatings - Marrocco, T.; Hussain, Tanvir; McCartney, D. G.; Shipway, P. H. (Springer Science Business Media, 2011)
The recent development of cold spray technology has made possible the deposition of highly reactive,oxygen sensitive materials, such as titanium, without significant chemical reaction of the powder, modificationof particle microstructure and with minimal heating of the substrate. However, the presence ofinterconnected pathways (microscale porosity) within the deposit limits the performance of the metalliccoating as an effective barrier to corrosion and substrate attack by corrosive media is usually inevitable.The aim of the present study was to investigate the effects of processing, including a postspray lasertreatment, on the deposit microstructure and corrosion behavior. Commercially pure titanium (CP Ti)was deposited onto a carbon steel substrate, using a commercial cold spray system (CGTTM Kinetiks4000) with preheated nitrogen as both the main process gas and the powder carrier gas. Selected coatingswere given a surface melting treatment using a commercial 2 kW CO2 laser (505 Trumpf DMD). Theeffect of postdeposition laser treatment on corrosion behavior was analyzed in terms of pore structureevolution and microstructural changes. Optical microscopy, scanning electron microscopy, and x-raydiffraction were employed to examine the microstructural characteristics of the coatings. Their corrosionperformance was investigated using electrochemical methods in 3.5 wt.% NaCl (ASTM G5-94 (2004)).As-sprayed titanium coatings could not provide favorable protection to the carbon steel substrate in theaerated NaCl solution, whereas the coatings with laser-treated surfaces provided barrier-like properties.